Aspects of Lyophilization of Cardiac Bioimplant - Nataliia Shchotkina (Innovative Biosystems and Bioengineering, 2021)
The use of implants of biological origin in clinical practice has led to the search for methods of long-term storage of tissues without damaging their functional and structural characteristics. Xenografts (extracted from pericardium of pigs, horses, bulls) are drawing more and more interest. The bovine pericardium is exposed to chemical and physical factors providing complete purification of tissue from cells and their components. Such scaffolds are protein (collagen) complexes that fully replicate the microstructure of the pericardial tissue. Lyophilisation ensures long-term preservation of the extracellular matrix properties. The principle of the method is in drying pre-frozen tissue, in which water is sublimated. The method is intended for storage, transportation, and the subsequent use of the bioimplant in clinical practice. However, the lyophilization process may be accompanied by various undesirable factors that can lead to denaturation of the matrix protein or loss of its functionality and structure. To preserve the natural microstructure, stabilizers or various modifications (slow/fast freezing, reducing the degree of supercooling, etc.) of the lyophilization process are applied to biological prostheses. In this review, the main processes of lyophilization of biological tissue are described, which can affect the operation of a cardiac implant. A deep understanding of the parameters of the lyophilization process is crucial for creation of stable tissue grafts and their subsequent long-term storage.